Hidrodestrllates antifungal effect from Zingiber officinale Roscoe on Moniliophthora roreri (Cif 82 Par) - Joya-Dávila, José Gregorio; Ramírez-González, Sandra Isabel; López-Báez, Orlando; Alvarado-Gaona, Álvaro Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The frosty pod rot caused by the fungus Moniliophthora roreri (Cif. & Par) is the main disease of cocoa in Latin America, while the measures for their sustainable management are still limited. Based on previous reports the aim of this study, was to optimize the extraction process by the distillation of Zingiber officinale, and evaluating in vitro their antifungal effect on M. roreri, Eight hidrodestilleted were prepared with fresh material (300 and 600 g/L) and sun dried (45 and 90 g/L), with two solvents (Water:Alcohol ratio 10:1 and 10:0) for which the cultivation technique used, was test tubes in liquid medium (water extracted from cocoa) with conidia fungus. It was added each hidrodestillated of Z. officinale in ratio (1 :1 v/v), by which determines its effect on the formation and germination of the fungus conidia in five observation times (0, 24, 48, 72 and 96 hours).The results indicate that all hidrodestillators of the Z. officinale show metabolites with inhibitory effects on the variables evaluated, with thel5 (dried Z. officinale, 45 g/L ratio 10:1 water: alcohol) being the best treatment, due that it reaches from 88% to 100% control over the Conidias formation and germination respectively, with regard to the absolute witness at 72 hours, being also possible to optimize the distillation extraction by using 45 g/L dry material and employ solvent waterzalcohol in a 10:1 relationship.